Could the service consumption-production interface lift national logistics performance? - Wong, Wai Peng; Soh, Keng Lin; Sinnandavar, Chandra Mohan; Mushtaq, Naveed (Elsevier B.V., 2016)
This research contains a four layer framework which aims to identify the performance factors. The proposed model is tested and validated by 43 samples data by using variance-based SEM approach (PLS). It extends the body of research in integration and sustainable supply chain management. The four layers contain the integration factors, inland depot service quality, hauliers firms’ sustainable performance and national logistics performance. A questionnaire survey and two expert groups were deployed. Survey respondents were managers of haulage companies which made up 30% of the 140 active companies. Annual revenue for a firm ranges from Ringgit Malaysia 1.25 million to 5 million. Each firm made an average of 170 trips to the depots daily. The theoretical contributions are the validation of industry-derived integration factors and the unwitting revelation that the stakeholder theory is unfazed by the downside of the agency theory. This surprisingly confirmed depot could still influence hauliers favourably. The practical contributions are the usefulness of the integration factor questionnaire items for future haulage studies, and that depots and hauliers should collaborate to lift national logistics performance.